The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.ijdevneu.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is implicated in arsenic‐induced neural tube defects in chick embryos

Abstract: The potential of arsenic to induce neural tube defects (NTDs) remains a topic of controversy. In our previous study, oxidative stress and altered DNA methylation were observed in arsenic-exposed animal models. However, the correlation between these conditions was not fully understood. Therefore, our present aim was to determine whether arsenic exposure results in altered reactive oxygen species levels that affect DNA methylation and may contribute to NTDs in chick embryos. We demonstrated that arsenic-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…These results are similar to those from previous studies that showed iAs-induced structural malformations in the chick (Han et al 2011) and mouse embryo models (Chaineau et al 1990; Tabocova et al 1996). The iAs-induced malformations in mouse have also been shown to be associated with systems-level changes in gene expression (Robinson et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those from previous studies that showed iAs-induced structural malformations in the chick (Han et al 2011) and mouse embryo models (Chaineau et al 1990; Tabocova et al 1996). The iAs-induced malformations in mouse have also been shown to be associated with systems-level changes in gene expression (Robinson et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…To further strengthen this, we show that the same in vitro / in vivo manipulations of MnSOD also ameliorate diabetes-induced increase in retinal Tet activity. Consistent with this, Tets are activated under high oxygen conditions by alpha ketoglutarate, a cofactor produced in the citric acid cycle [36], and N-acetyl-l-cysteine, a known antioxidant, diminishes global DNA hypomethylation [37]. …”
Section: Discussionmentioning
confidence: 96%
“…ventral body wall defects) were reported in embryos exposed in utero to cadmium [37]. Another study documented arsenic-induced altered expression of DNMTs and MBDs, a significant decrease in S-adenosylmethionine (SAM) (the source of the “methyl” group for DNA methylation), and global DNA hypomethylation - resulting in neural tube defects in exposed embryos [38]. …”
Section: Introductionmentioning
confidence: 99%